Kilovolt Peak Meter Design as a Calibrator of X-Ray Machine - Hanifah Rahmi Fajrin; Zaipul Rahmat; Djoko Sukwono (Institute of Advanced Engineering and Science, 2019)
This research aimed to design the KvP meter for checking the error of output voltage from X-Ray machine with the range of 50-70 KvP. It used Arduino Gelatino microcontroller programmed with Arduino IDE software as data processor of detector result. The detector was designed based on the physics principle using material attenuation coefficient namely aluminum whose good effect in reducing the energy level of X-ray photons. Thus, the photodiode sensor only read the effective energy of the X-ray energy. Based on the radiation intensity ratio through the aluminum filter with 0.25 mm and 0.5 mm thickness, it is better to measure X-ray tube voltage non-invasively The KvP Meter was tested by setting duration of X-ray exposure that was 0.3 second, tube current was 10 mA, and KvP Meter distance from collimator was 90 cm. A prototype unit was made, and the performance was tested in terms of error and precision. After testing and analyzing the data, the error result was less than 5.1% with the highest measurement precision of ± 1.50. It is generally concluded that this equipment can be used to measure the voltage of the X-ray tube.